Prostate cancer screening behaviors and its related cognitive psychological factors among men over 50 years of age using the Health Belief Model - Majid Barati; Saeed Bashirian; Mohammad Ali Amirzarghar; Amirabbas Mousali; Mohammad Hassan Saatiasr (Tehran University of Medical Sciences, 2018)
Background & Aim: Prostate carcinoma is the most common cancer among men and the second lethal cancer. The present study aimed to investigate the prostate cancer screening behaviors and its related cognitive psychological factors among men over 50 years of age using the health belief model. Methods & Materials: This cross-sectional study was performed on 300 men over 50 years of age in Hamadan, selected by cluster sampling method. Data collecting tool was a questionnaire consisted of three sections: demographic information, prostate cancer screening behaviors and health belief model constructs. Data were analyzed using Chi-square test, Fisherchr('39')s exact test and logistic regression through the SPSS software version 18. Results: Findings revealed that 12% and 9% of the participants reported having a digital rectal examination (DRE) and prostate specific antigen (PSA) testing respectively. Perceived benefits and perceived barriers were the predictors of prostate cancer screening behaviors (P<0.05). Also, there was a significant relationship between prostate cancer screening behaviors and age and a history of prostate problems (P<0.05). Conclusion: Given that the health belief model is effective in predicting prostate cancer screening behaviors, using these findings in designing educational interventions for people over 50 is recommended.